Effective Software Maintenance and Evolution / A Reuse-Based Approach - Jarzabek Stanislaw (Auerbach Publishers Incorporated, 2007)
This book gives a rare and fascinating sketch of techniques for maintenance and evolution of successful software. Foreword, Acknowledgements, Introduction, Conventional Methods of Software Maintenance and Evolution, Static Program Analysis Methods, Reverse engineering Methods, Model Based Design for Ease of Maintenance, Evolution of Versions and Configuration Management, Limits of Conventional Techniques, Reuse-Based Software Maintenance and Evolution, Step-by-Step Introduction to XVCL, Software Similarities: Symptoms and Causes, Evolution with the Mixed-Strategy Approach, Scaling Up the Mixed-Strategy Approach, Other Techniques Related to XVCL, Evaluation of the Mixed -Strategy Approach, Conclusions, Index.